2016
DOI: 10.1590/1981-7746-sip00111
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação De Programas De Formação Profissional Em Saúde: Construção E Validação De Indicadores

Abstract: Resumo Este artigo teve como objetivo elaborar um instrumento qualificador visando contribuir para o monitoramento e a avaliação do Programa de Residên-cia Multiprofissional em Saúde da Família. Foi um estudo avaliativo exploratório desenvolvido em duas fases: a primeira, constituída pela construção e validação de face do modelo lógico e da matriz de indicadores, por meio de análise documental e da técnica de consenso grupo nominal. Essa primeira fase, por sua vez, aconteceu em dois momentos, pré e pós-reunião… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
19

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 8 publications
0
7
0
19
Order By: Relevance
“…The use of financial resources and the rationalization of human resources are the great challenge to the management of CEOs and evaluations bring important contributions [20]. The situation of CEO's endodontics has shown that advances in the introduction of hard technology, with the use of equipment capable of delivering quality and speed to endodontic services, where professionals who perform it are qualified; however, endodontics is still the specialty with the highest queue in services, a fact that can have a decisive impact on the evolution of caries disease and dental loss.…”
Section: Discussionmentioning
confidence: 99%
“…The use of financial resources and the rationalization of human resources are the great challenge to the management of CEOs and evaluations bring important contributions [20]. The situation of CEO's endodontics has shown that advances in the introduction of hard technology, with the use of equipment capable of delivering quality and speed to endodontic services, where professionals who perform it are qualified; however, endodontics is still the specialty with the highest queue in services, a fact that can have a decisive impact on the evolution of caries disease and dental loss.…”
Section: Discussionmentioning
confidence: 99%
“…How can it be possible that professionals from different specialties are formed based on a common axis? 26 In fact, many institutions in Brazil still favour a disciplinary health model, with priority for specialized training, organized under the "Flexnerian" aegis, in a fragmented, mechanistic, Cartesian and biologically centred model 19,21,[43][44][45][46] . It is then considered as social change, specifically in health policy, "to materialize the paradigms of 'making health' linked to social determinants and denying the Flexnerian reports" (p. 17) 43 .…”
Section: Teaching-learning Concepts and Evaluation Methodsmentioning
confidence: 99%
“…O intuito, assim, é aumentar a validade do constructo e fortalecer a replicação analítica dos estudos de caso, desenho de pesquisa que parte da teoria para a empiria 17 . Métodos participativos, como as técnicas de consenso 18,19 , têm sido utilizados com essa finalidade.…”
Section: Methodsunclassified